2016
DOI: 10.1007/s11886-016-0757-2
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in the Assessment of Patients with Rheumatologic Diseases

Abstract: Cardiovascular disease is an important extra-articular manifestation of rheumatologic diseases leading to considerable mortality and morbidity. Echocardiography emerges as a useful non-invasive technique for the screening and evaluation of cardiac involvement in these patients. With the technological advancement in echocardiographic techniques, we have gained a greater appreciation of the prevalence and nature of the cardiac involvement in these patients, as detection of subclinical disease is increasingly fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
1
8
0
1
Order By: Relevance
“…Many imaging tools such as coronary artery calcification by multi-slice computed tomography [39], intima–media thickness by carotid ultrasound [40], arterial stiffness with aortic pulse wave velocity or arterial augmentation index, ankle–brachial index [4143], and echocardiography [44], have been proposed to measure subclinical vascular damage in RA. Among these, only carotid ultrasound has been included in EULAR recommendations for clinical practice, based on the evidence that carotid plaques in RA are associated with disease duration, disease activity, and ischemic heart disease with poor CVD-free survival [4547].…”
Section: Introductionmentioning
confidence: 99%
“…Many imaging tools such as coronary artery calcification by multi-slice computed tomography [39], intima–media thickness by carotid ultrasound [40], arterial stiffness with aortic pulse wave velocity or arterial augmentation index, ankle–brachial index [4143], and echocardiography [44], have been proposed to measure subclinical vascular damage in RA. Among these, only carotid ultrasound has been included in EULAR recommendations for clinical practice, based on the evidence that carotid plaques in RA are associated with disease duration, disease activity, and ischemic heart disease with poor CVD-free survival [4547].…”
Section: Introductionmentioning
confidence: 99%
“…In RA patients, the asymptomatic reduction in cardiac systolic function is about 3 times more than non-RA population 24 . Study has suggested that RA patients with reduced LVEF% are less likely received antirheumatic drugs such as methotrexate and corticosteroids 26 .…”
Section: Discussionmentioning
confidence: 96%
“…Valvular abnormalities mainly involving the mitral and aortic valve with mild to moderate regurgitation in RA patients 24 , the mechanisms might be due to the chronic inflammatory process and fibrosis of the cardiac valves 25 . Our results showed that the prevalence of mitral regurgitation was slightly more than that of the control group, but the difference was not significant between 2 groups, we found the prevalence of mitral regurgitation was correlated with ESR in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 24 h-Holter, 2-dimensional speckle tracking imaging, nuclear angiography, and cardiovascular magnetic resonance could provide more valuable information for discovering early CI in patients with SSc. [13,17,18] We did not schedule too many medical assessments. Rapid targeted treatment (a pacemaker implantation) was administered after a definitive diagnosis to prevent adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%